Numerical Study of Fuselage Impact on Acoustic Characteristics of a Helicopter Rotor - Abalakin, Ilya A.; Bobkov, Vladimir G.; Kozubskaya, Tatiana K. (Supercomputing Frontiers and Innovations, 2022)
The paper presents the results of the simulation of unsteady turbulent flow generated by helicopter main rotor in the presence of the fuselage with an emphasis on the analysis of the influence of the fuselage on the rotor-induced flow and the rotor-generated acoustic field. The Reynolds-averaged Navier–Stokes equations with the Spalart–Allmaras turbulence model are used to simulate the Caradonna–Tung rotor and ROBIN fuselage interaction in hovering flight. The governing equations are discretized using the vertex-centered control volume method on mixedelement unstructured meshes with the sliding mesh technology to treat the rotor. The acoustic field generated by the rotor+fuselage interaction is comparatively analyzed against the case of an isolated rotor. It is found that the presence of fuselage significantly changes the rotor-generated acoustics. In particular, the presence of the fuselage noticeably distorts the directivity of acoustic radiation and increases the overall sound pressure level under the fuselage up to 20 dB, emphasizing the importance of the influence of fuselage on the helicopter acoustics.